Equity of subway accessibility: A perspective from work commute trips. (December 2022) - Guo, Sihui; Pei, Tao; Wang, Xi; Song, Ci; Chen, Xiao; Chen, Jie; Shu, Hua; Liu, Yaxi; Wu, Mingbo
Abstract: The equity of subway accessibility is of great concern to policy makers. This study measures the subway accessibility of work commute trips for commuters. Based on multi-source geographic data, we calculated the subway accessibility by extending traditional two-step floating catchment area method based on locations to trips. The results show that: (1) subgroups including women, younger people, and those who lived in lower-priced housing areas and worked in areas with less high-paying jobs were disadvantaged in subway accessibility; (2) people live or work in areas far from the city center had lower subway accessibility; and (3) the subway accessibility is influenced by people's socio-economic status and the environmental characteristics of their home and the workplace. The findings of this study provide evidence to show the impact of subways on transport equity in developing countries and will be of practical value when undertaking city or transportation planning in the future.